Primary actinomycosis of vulva with inguinal lymphadenopathy - Anand J Asia; Vaibhav N Tapre (Wolters Kluwer Medknow Publications, 2016)
Actinomycosis is a chronic suppurative granulomatous infection of subcutaneous tissues caused by bacterium Actinomyces israelii. It is a normal commensal of the oral cavity, gastrointestinal tract, respiratory tract, and vagina. Infection is first established locally by breach of mucosal barrier during various procedures, aspiration, trauma, or human bite. Rarely, it may spread through hematogenous and lymphatic system. We present a case of actinomycosis involving the vulva, extending to the inguinal region along with inguinal lymphadenopathy. Involvement of vulva by actinomycosis is uncommon in literature.